Thermotolerant micro-organisms in Consolidated Bioprocessing for ethanol production: A review - Mienda, Bashir Sajo; Shamsir, Mohd Shahir (Research in Biotechnology, 2013)
Microorganisms that withstand high temperatures (thermotolerant) will continue to gain global significant prominence in consolidated bioproduction of ethanol. Consolidated bioprocessing (CBP) technology, is an approach that merged together enzyme production, saccharification and fermentation in a single vessel. It offers considerable advantages for the production of bioethanol. It seems promising because of its reduction in utilities, substrate and raw material simplification during operation, making it cost effective. High temperature CBP is preferred, because cellulolytic optimum enzyme performances occur at elevated temperature of around 50Ã¢ÂÂ°C. While on the other hand, optimum microbial fermentation occur best at temperature between 28Ã¢ÂÂ°C - 37Ã¢ÂÂ°C. This necessitates the search for more thermo tolerant micro-organisms as suitable candidates for CBP. Despite the advances seen in this technology, it uses only highly engineered microbial strains, which poses public health risks and environmental concern. As promising as the approach might be, there are, as yet, no wild types microbial strain has been isolated that perform CBP at the required elevated temperatures. This review will focus on the recent features of CBP technology, its advantages and drawbacks towards the production of bioethanol, and provide selected characteristics features of some thermotolerant micro-organisms for the process compatibility. Furthermore, perspectives, challenges and emerging new directions were also briefly highlighted.